Echocardiographic based cardiac evaluation in children with severe acute malnutrition - Arshad, Muhammad Sohail; Khan, Saadia; Ali, Ibad; Arshad, Reema; Abbas, Asad; Irshad, Sundas (Journal of the Pakistan Medical Association, 2022)
Objective: To identify echocardiography-based myocardial changes in children with severe acute malnutrition. Method: The prospective study was conducted from January to November 2020 at a territory care paediatric hospital in Multan, Pakistan, and comprised severe acute malnutrition patients of either gender aged 1-60 months and an equal number of matching healthy controls. Malnutrition was categorised using the World Health Organisation criteria. Echocardiographic evaluation was done by expert cardiologists. Values for ejection fraction shortening, left ventricular mass, E/A wave ratio as well as mitral and tricuspid annular plane systolic excursions were noted. Data was analysed using SPSS 21. Result: Of the 150 subjects, 75(50%) each were cases and controls. Age and gender were not significant different between the groups (p>0.05). Left ventricular mass and left ventricular mass index with body surface area were significantly reduced in the cases compared to the controls, and the same was the case with left ventricular ejection fractional shortening (p<0.05). There was no significant difference between the groups in terms of E/A wave ratio as well as mitral and tricuspid annular plane systolic excursions (p>0.05). Among the cases, cardiac evaluation showed 26(34.6%) were kwashiorkor and 49(65.3%) were marasmic patients. Conclusion: Left ventricular parameters in malnourished children were found to be reduced. As such, the assessment of these parameters may appear to be a significant indicator for timely identification of cardiac malfunction in severe acute malnutrition cases. Key Words: Severe acute malnutrition, Myocardial performance index, Ejection fraction, Fractional shortening, Cardiac function.